Acute fatty liver of pregnancy cases in a maternal and child health hospital of China: Three case reports. Issue 29 (17th July 2020) - Wang, Ling; Gan, Quan; Du, Shuguo; Zhao, Yun; Sun, Guoqiang; Lin, Ying; Li, Ruyan
Abstract: Rationale: Acute fatty liver of pregnancy (AFLP) is extremely hazardous to pregnant woman in the 3rd trimester of pregnancy. AFLP has an insidious onset and nonspecific experimental indicators, which therefore is difficult to be diagnosed. Patient concerns: Case 1 was transferred to our hospital for hypertensive disorders complicating pregnancy at gestation of 38 weeks + 3 days. Case 2 was transferred to our hospital for suspicious fetal heart monitoring response at gestation of 36 weeks + 4 days. Case 3 was transferred to our hospital for prelabor rupture of membranes at gestation of 37 weeks + 1 days. Diagnosis: The diagnosis of AFLP was based on the Swansea criteria. Interventions: All 3 cases were delivered by cesarean section, and they were all transferred to intensive care unit for further treatment. Cases 2 and 3 were subjected to plasma exchange and continuous renal replacement therapy. Outcomes: In this study, all 3 patients were initially diagnosed as gastritis. In addition, case 1 was diagnosed as preeclampsia and her AFLP was misdiagnosed with postpartum hemorrhage after cesarean delivery. Case 2 was admitted to the hospital for intrahepatic cholestasis of pregnancy and fetal distress, but we considered it as AFLP before delivery. Case 3 was treated according to severe intrahepatic cholestasis of pregnancy, but we rediagnosed it as postpartum hemorrhage and disseminated intravascular coagulation after cesarean delivery. Neonatal asphyxia and complications were not found. All of the 3 cases were fully recovered and discharged from our hospital. Lessons: If there are multiple risk factors including vomiting, abdominal pain, and fetal distress, AFLP should be highly suspected. Early diagnosis, especially before termination of pregnancy, is the key to successful treatment of AFLP.